STUDIES ON POPULATION PARAMETERS AND SOME ASPECTS OF BIOLOGY OF SIGANUS CANALICULATUS (PARK, 1797) (PISCES: SIGANIDAE) FROM ANDHRA PRADESH, INDIA - DEEPTI, V A ISWARYA; RAVALI, V; SUJATHA, K (Journal of the Inland Fisheries Society of India, 2026)
Siganus canaliculatus (Park, 1797), though primarily marine, also inhabits estuaries and has been successfully introduced into freshwater lakes and pond habitats as well. Due to its occurrence in a wide range of habitats and importance to both fisheries and aquaculture, studies on some aspects of biology, including length-weight relationships, population parameters, and various aspects of reproductive biology, were conducted. In the present study, 1560 specimens of size range 54-267mm TL were collected during the period July 2017-June 2019 from the coastal waters of the north Andhra region. The present study provides biological reference points that are required for fishery management in this region.